Myelopoietic cell proliferation in granulocytopenia of refractory anaemia and preleukemia states with hyper-plastic bone marrow - Fischer, M; Mitrou, P S; Hübner, K (Klinische Wochenschrift, 1976)
Myelopoiesis in healthy subjects and in 8 cases of refractory anaemia or preleukemia states was studied by the combined cytophotometric-autoradirgraphic method. Granulocytopenia was present in 7 of 8 cases. The results can be summarized as follows: 1. Mature myelocytes of healthy persons are a mainly differentiating cell population with a low labelling index (3-10%) and a high incidence in G1-Phase. 2. The proliferating immature granulopoietic cells of the patients with neutropenia showed a reduced labelling index with 3H-thymidine as a result of an arrest of these cells in G1 (6 of 8 cases). 3. A similar result was obtained in the study of the hyperplastic myelopoiesis of an other patient with preleukemia and normal granulocyte count in peripheral blood, with the disturbance of cell proliferation preceding the symptom neutropenia. 4. Finally in only one case an increased frequency of myelopoietic cells in G2-phase was found suggesting an arrest of cell proliferation in the premitotic phase.